2010
DOI: 10.1185/03007991003689381
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the cost-effectiveness of biphasic insulin aspart 30 in type 2 diabetes

Abstract: Although cost-effectiveness data on BIAsp 30 are scarce the majority of the analyses identified in this review suggest that BIAsp 30 is likely to be cost-effective compared to insulin glargine and biphasic human insulin across a wide range of settings, and under certain circumstances would be a dominant treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Please note that owing to the lack of adequate sample sizes, we did not perform meta-analysis on other specific regions such as the premotor cortex (PC), the anterior temporal lobe (ATL) and the angular gyrus (AG)], stimulation parameters of the TMS protocols [i.e., methods of brain region localization, stimulation types (further analysis on cTBS but not iTBS (only one study) was conducted considering the inadequate sample sizes), timing, frequencies, and intensities], and experimental designs (i.e., control conditions and group design types) are crucial for the examination of TMS effects on language performance in healthy participants. Effect sizes with an associated 95% confidence intervals (CI) were calculated when at least two studies were available for a particular estimate (see also Valentine et al, 2010 ). The analysis-structure of both the overall and the moderator analyses are summarized in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Please note that owing to the lack of adequate sample sizes, we did not perform meta-analysis on other specific regions such as the premotor cortex (PC), the anterior temporal lobe (ATL) and the angular gyrus (AG)], stimulation parameters of the TMS protocols [i.e., methods of brain region localization, stimulation types (further analysis on cTBS but not iTBS (only one study) was conducted considering the inadequate sample sizes), timing, frequencies, and intensities], and experimental designs (i.e., control conditions and group design types) are crucial for the examination of TMS effects on language performance in healthy participants. Effect sizes with an associated 95% confidence intervals (CI) were calculated when at least two studies were available for a particular estimate (see also Valentine et al, 2010 ). The analysis-structure of both the overall and the moderator analyses are summarized in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…one study) was conducted considering the inadequate sample sizes), timing, frequencies, and intensities], and experimental designs (i.e., control conditions and group design types) are crucial for the examination of TMS effects on language performance in healthy participants. Effect sizes with an associated 95% confidence intervals (CI) were calculated when at least two studies were available for a particular estimate (see also Valentine et al, 2010). The analysis-structure of both the overall and the moderator analyses are summarized in Figure 2.…”
Section: Data Analysesmentioning
confidence: 99%
“…It is recommended that if lifestyle modification and full tolerated doses of one or two oral glucose lowering drugs (OGLDs) fail to achieve or sustain glycemic goals, then insulin therapy should be initiated [ 10 ]. Over the past decade, insulin analogs have gained recognition since they offer numerous advantages over the traditional preparations with regard to blood glucose variability, number of injections needed, patient satisfaction, and life expectancy [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Palmer and colleagues have shown that switching from traditional preparations to biphasic insulin Aspart 30 (BIAsp 30) would result in an additional $ 9000 in terms of life-time direct medical costs [ 15 ]. A number of previous studies have delineated the efficacy, safety, and cost-effectiveness of BIAsp 30 in patients with diabetes [ 14 – 17 ]; yet the cost-effectiveness of such therapy has not been explored in Iran. The aim of the present piggyback study was to investigate the cost-effectiveness of BIAsp 30 using the data from a clinical trial Iranian patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Cost-effectiveness of biphasic insulin aspart 30 compared with glargine has been summarized in a systematic review utilizing the validated CORE diabetes model, which concluded that treatment with biphasic aspart is associated with increased quality-adjusted life expectancy in several countries, resulting in incremental cost-effectiveness ratios of approximately USD 46500 and GBP 6950 per qualityadjusted life year gained in the United Stated and the United Kingdom, respectively [13]. On the other hand, combination of glargine with oral antidiabetic agents was shown to be cost-effective in comparison to monotherapy with premixed insulin in insulin-naïve patients in Canada [14].…”
mentioning
confidence: 99%